2011
DOI: 10.3346/jkms.2011.26.9.1227
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Syndrome and Peripheral Polyneuropathy in Patients with End Stage Kidney Disease

Abstract: This study was designed to identify the causes of the development of carpal tunnel syndrome (CTS) associated with end stage kidney disease (ESKD). A total of 112 patients with ESKD, 64 on hemodialysis (HD) and 48 on peritoneal dialysis (PD), were enrolled. The duration of ESKD and dialysis, the site of the arteriovenous (A-V) fistula for HD, laboratory data such as blood urea nitrogen, creatinine, and beta-2-microglobulin were determined. Clinical evaluation of CTS and electrophysiological studies for the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 14 publications
1
41
1
1
Order By: Relevance
“…Frequency of CTS in patients undergoing HD is reported as 8% to 31% (1). In the present study, we found that 43 (45,2%) of the patients on HD therapy had complaints related to CTS.…”
Section: )supporting
confidence: 50%
See 1 more Smart Citation
“…Frequency of CTS in patients undergoing HD is reported as 8% to 31% (1). In the present study, we found that 43 (45,2%) of the patients on HD therapy had complaints related to CTS.…”
Section: )supporting
confidence: 50%
“…It is the most common mononeuropathy in patients with end stage renal disease (ESRD) with a frequency of 8% to 31% (1). With the improvements in the techniques of HD, the number of patients suffering from HD related CTS has also increased (3) and the prevalence of CTS correlates with the duration of HD (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference in the occurrence of subclinical median nerve entrapment between hands with and without fistulas. Contradictory findings regarding the origin of CTS and the role of amyloidosis, AV fistulas, tumoral calcinosis, β2-microglobulin, or "theft" of blood from the distal limbs, have been reported [3,26,27,29,30]. We postulate that in many cases median NCS changes in hemodialysis patients are associated with an underlying polyneuropathy, and are not due to entrapment damage.…”
Section: Discussionmentioning
confidence: 76%
“…It is important to note that the minimal F-wave reflects the function of the entire motor axon pathway, whereas other nerve conduction parameters provide information about restricted segments of nerve fiber pathways [11]. In patients with fistulas in the hands, the location of fistulas may induce a "theft" of blood from the distal limbs, and influence fiber impulse volley through [3,26,27,29,30]. The median nerve, owing to its anatomical position, provides greater nerve fascicular susceptibility to the location of the fistula compared with the ulnar nerve.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies offer conflicting evidence and suggest that no difference in the frequency of CTS occurs with either the duration of dialysis or the side of the arterio-venous fistula. 16 Some authors have investigated nerve conduction study methods that demonstrate reliability in distinguishing CTS from background polyneuropathy. 17 We identified a greater than anticipated number of iatrogenic neuropathies.…”
Section: Discussionmentioning
confidence: 99%